Measuring the impact and the extent of satisfaction of owners of small and medium enterprises benefiting from the support services provided by the Jordanian Small and Medium Enterprises Corporation during the period (2016-2022) - Alsalaheen, Osama Suliman; Alzubaidi, Ameen Sulieeman; Shammout, Ameen Osama (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to measure the level of satisfaction of the beneficiaries of the support programs provided by the Jordanian Corporation for the Development of Economic Enterprises and link that to the impact in terms of the increase in each of ( productive capacity, employment, the sales, exports) to beneficiaries during the period ( 2016-2022 ) , where addresses and phone numbers were obtained for about (250) beneficiaries of the supportive programs (13 programs) provided by the Jordan Corporation for the Development of Economic Enterprises in Jordan during the period 2016-2022, where they were distributed The questionnaire was addressed to the beneficiaries, and about (110) beneficiaries responded. The descriptive approach was adopted In analyzing the data of the study, the analysis was also done using the SPSS  In this study, 5 axes were relied upon in measuring satisfaction, which are (equipment quality reliability, ease and speed of response) trust and safety axis, and staff axis (The institution)., the study found that there is a correlation in achieving the increase in (production, revenue, employment, exports) and between items (the level of satisfaction in general). The study also found that the percentage of beneficiaries who answered that the reason for the increase in exports is due to the programs provided by the institution (87%) and the percentage of beneficiaries who answered that the reason for the increase in employment is due to the programs provided by the institution (90%) and the percentage of beneficiaries who answered that the reason for the increase in sales is due to the programs provided by the institution (91%) and the percentage of beneficiaries who answered that the reason for the increase In production, due to the programs provided by the institution, it reached (95%), as the study found, and by comparing the 5 axes that were previously reviewed, it was shown that the (trust and safety) axis ranked first, achieving 85.8%.
Keywords: Level of satisfaction; impact of support programs; owners of small and medium enterprises